8 Sandpiper way - Macomber, Debbie; Mira Books (Don Mills, Ont : MIRA Books, 2008)
Cedar Cove is shocked after Pastor Dave Flemming is accused of stealing jewelry. His wife, Emily, doesn't know what to believe, especially since Dave is being so evasive. Then she finds an earring in his pocket. Could he have stolen it--or is he having an affair?
Adult.
Keywords: Cedar Cove (Wash. : Imaginary place) -- Fiction; Clergy -- Fiction; Community life -- Fiction; Married people -- Fiction; Spouses of clergy -- Fiction; Washington (State) -- Fiction; Love stories